Translation Methods in A Walk To Remember Novel Translated Into Kan Kukenang Selalu - Syafrizal Syafrizal; Cucum Rohmawati (English Department - University of Sultan Ageng Tirtayasa, 2018)
This research is aimed to identify and describe the translation methods used in translating novel A Walk to Remember into Kan Kukenang SelaluChapter I and Chapter II. The data were analyzed through a translation methodstated by Newmark (1988), they were Word for Word Translation, Literal Translation, Faithful Translation, Semantic Translation, Adaptation Translation, Free Translation, Idiomatic Translation, and Communicative Translation. Descriptive qualitative method was implemented in this research. The data were taken from each sentence written in English (as the Source Language/SL) into Indonesian (as the Target Language/TL). Finally, the writer found that: 1) all types of translation methods occurred in A Walk to Remember into Kan Kukenang SelaluChapter I and Chapter II; they are they were Word for Word Translation (8%), Literal Translation (14%), Faithful Translation (12%), Semantic Translation (20%), Adaptation Translation (10%), Free Translation (18%), Idiomatic Translation (10%), and Communicative Translation (8%). The most frequent types of translation method found in A Walk to Remember into Kan Kukenang SelaluChapter I and Chapter II were Semantic Translation (20%) and Free Translation (18%).Keywords: Translation, Translation Methods, Novel,